Testing Models of MCT Reactivation vs. Duplex Formation in the Kumuan and Garwhal Himalaya, India - Célérier, Julien; Harrison, T Mark; Dunlap, William J (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 110